(untitled) (Bangladesh Journal of Zoology, 2021)
The study was conducted on species availability and infrastructure analysis of four different wholesale fish markets in Dhaka City. Two markets were selected from Dhaka South City Corporation, Showari Ghat and Jatrabari fish market, and two from Dhaka North City Corporation, Karwan Bazar and Abdullahpur fish market. The investigation was carried out from November 2018 to October 2019. Questionnaire based survey, FGDs (Focus Group Discussion) and KIIs (Key Informant Interviews) were conducted to get quantitative and qualitative data for present study. A total number of 62 fishes and 6 crustacean species were recorded during the study period. Among all species, 39 freshwater, 10 marine and 13 exotic fishes were recorded. Infrastructure facilities were very poor for all four markets in the matter of hygiene and quality control. Fish shades were not enough, improper sanitation and drainage system indicates the possibilities of disease transmission and deteriorate fish quality. Electricity and water supplies were good but no system was present to determine the distillation of those supplied water. Thus, infrastructural condition of the markets does not support a hygienic condition for fish marketing to provide quality fish and fish byproducts. The study highlighted the need for national initiatives, awareness building, and law implementation for improving the wholesale markets infrastructure to a minimum standard so that fish trade could provide good quality to the people of Dhaka City Bangladesh J. Zool. 49 (2): 289-300, 2021